Role of Sugar and Sugar Substitutes in Dental Caries: A Review. (29th December 2013) - Gupta, Prahlad; Gupta, Nidhi; Pawar, Atish Prakash; Birajdar, Smita Shrishail; Natt, Amanpreet Singh; Singh, Harkanwal Preet
Abstract : Dental caries is a chronic disease which can affect us at any age. The term "caries" denotes both the disease process and its consequences, that is, the damage caused by the disease process. Dental caries has a multifactorial aetiology in which there is interplay of three principal factors: the host (saliva and teeth), the microflora (plaque), and the substrate (diet), and a fourth factor: time. The role of sugar (and other fermentable carbohydrates such as highly refined flour) as a risk factor in the initiation and progression of dental caries is overwhelming. Whether this initial demineralization proceeds to clinically detectable caries or whether the lesion is remineralized by plaque minerals depends on a number of factors, of which the amount and frequency of further sugars consumption are of utmost importance. This paper reviews the role of sugar and sugar substitutes in dental caries.